2023
DOI: 10.1159/000529357
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 as an Independent Risk Factor for Weight Loss in Older Adults Living in Nursing Homes

Abstract: Introduction In nursing homes, where residents are at elevated risk for malnutrition, the specific additive effect of the coronavirus disease 2019 (COVID-19) on weight loss has not yet been adequately evaluated. This study aimed to determine the factors independently associated with weight loss in nursing home residents who survived the first wave of the COVID-19 pandemic, whether they have contracted COVID-19 or not. Methods This research was a retrospective study conducted in three nursing homes. Residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
2
2
Order By: Relevance
“…However, it is surprising that COVID-19 infection in the Cvijetić et al [ 16 ] study participants did not show any impact on OSA prevalence, weight loss, or nutritional status. This is contrary to the just published study in French nursing homes [ 47 ], where those infected with COVID-19 experienced about 5% of weight loss. Due to some other limitations of both studies, e.g., cross-sectional nature, a small number of participants in Keser et al [ 17 ], and the inability of BIA-ACC device to distinguish bone mass/quality in different skeletal regions, more studies such as this, where OSA can be diagnosed with one instrument (e.g., BIA or DXA) and conducted in critical populations (like nursing home residents), are warranted.…”
Section: Discussioncontrasting
confidence: 95%
“…However, it is surprising that COVID-19 infection in the Cvijetić et al [ 16 ] study participants did not show any impact on OSA prevalence, weight loss, or nutritional status. This is contrary to the just published study in French nursing homes [ 47 ], where those infected with COVID-19 experienced about 5% of weight loss. Due to some other limitations of both studies, e.g., cross-sectional nature, a small number of participants in Keser et al [ 17 ], and the inability of BIA-ACC device to distinguish bone mass/quality in different skeletal regions, more studies such as this, where OSA can be diagnosed with one instrument (e.g., BIA or DXA) and conducted in critical populations (like nursing home residents), are warranted.…”
Section: Discussioncontrasting
confidence: 95%
“…However, it is surprising that COVID-19 infection in the Cvijetić et al, [14] study participants did not show any impact on OSA prevalence, weight loss, or nutritional status. This is contrary to the just published study in French nursing homes [46], where those infected with COVID-19 experienced about 5% of weight loss. Due to some other limitations of both studies, e.g., cross-sectional nature, small number of participants in Keser, et al, [15], and inability of BIA-ACC device to distinguish bone mass/quality in different skeletal regions, more studies like this, where OSA can be diagnosed with one instrument (e.g., BIA or DXA) and conducted in critical populations (like nursing home residents), are warranted.…”
Section: Dietary Intake Nutritional Status and Osacontrasting
confidence: 93%
“…One US study explored weight changes among NH residents between March 2020 and May 2020 and found that all residents lost weight over this time period but residents who had COVID‐19 experienced 4.6% greater weight loss compared to non‐infected residents 17 . Potential mechanisms of this weight decrease include loss of taste and smell as a symptom of COVID‐19, as well as decreased mealtime assistance in quarantine 18,19 . NH residents are vulnerable to weight loss that could potentially lead to sarcopenia and nutritional deficiencies, fatigue, and subsequently, functional decline 10 .…”
Section: Discussionmentioning
confidence: 99%
“…17 Potential mechanisms of this weight decrease include loss of taste and smell as a symptom of COVID-19, as well as decreased mealtime assistance in quarantine. 18,19 NH residents are vulnerable to weight loss that could potentially lead to sarcopenia and nutritional deficiencies, fatigue, and subsequently, functional decline. 10 This study is limited by lack of precise weight trajectories that precludes a direct link with our findings, as weight loss is recorded in MDS data only if greater than 5% of body weight in the past 1 month or 10% in the past 180 days.…”
Section: Discussionmentioning
confidence: 99%